Faith Based Organizations as Instigators of Development: the contribution of Alfagems Secondary School in Morogoro (Tanzania) - Tadeusz Jarosz; Emmanuel Komba (Chrześcijaństwo-Świat-Polityka)
The study attempts to capture the impact of the religious element upon the development of a developing country. Due to the range of difficulties in outlining the field of study, from the outset it was assumed that the pro-developmental activity of Faith-Based Organizations (FBO) is carried out as an immanent part of the socio-economic processes of development. As FBO insiders target a given developmental goal, they start to act upon the secular proponents which are continually being reinforced from within the religious dimension. As indicated, this leads to measurable goals (the results of state examinations).